Chemical and histological comparisons between Brevoortia sp. (menhaden) collected in fall 2010 from Barataria Bay, LA and Delaware Bay, NJ following the DeepWater Horizon (DWH) oil spill. (December 2015) - Bentivegna, Carolyn S.; Cooper, Keith R.; Olson, Gregory; Pena, Edwin A.; Millemann, Daniel R.; Portier, Ralph J.
Abstract: Body burdens of PAHs were compared to histological effects in menhaden (Family: Clupeidae, Genus: Brevoortia ) collected in fall 2010 from Barataria Bay, LA (BBLA) and Delaware Bay, NJ (DBNJ). Barataria Bay was heavily oiled during the DeepWater Horizon (DWH) oil spill, while Delaware Bay although urbanized had no reported recent oil spills. GCMS analyses of pre-spill 2009, BBLA and DBNJ fish found predominantly C2/C3 phenanthrene (1.28–6.52 ng/mg). However, BBLA also contained five higher molecular weight PAHs (0.06–0.34 ng/mg DW). Fluorescent aromatic compound spectroscopy (FACS) of gastrointestinal (GI) tract tissue showed statistically higher levels of hydroxypyrene-like PAHs in DBNJ than BBLA fish. Histopathologic lesions were more prevalent in BBLA than DBNJ fish. The lesion prevalence (gill, trunk kidney, epidermis, stomach) in the BBLA menhaden were significantly higher and more severe than observed in the DBNJ menhaden. Reversible lesions included gill lamellar hyperplasia, adhesions, edema, and epidermal hyperplasia. The increased pigmented macrophage centers were indicative of activated macrophages responding to connective tissue damage or other antigens. The liver hepatic necrosis and renal tissue mineralization may well have undergone repair, but damage to the kidney nephrons and hepatic/biliary regions of the liver would be slower to resolve and apparently remained after elimination of PAHs. Therefore, a direct cause and effect between DWH oil spill and increased lesion prevalence in BBLA menhaden could not be established. Highlights: Impacts of the DeepWater Horizon (DWH) oil spill were studied in menhaden. PAH concentrations in tissues of Gulf of Mexico (GOM) and Mid-Atlantic coast fish were similar. Tissue damage as detected by histopathology was greater in GOM fish. Lesions in GOM menhaden could not be directly linked to exposure to DWH PAHs.